(untitled) (Research, Society and Development, 2021)
In spite of the substantial consumption of drugs by the world’s population, there is a large lack of orientation about how to adequately dispose of such products. This study refers to a problem that can affect public health, since these drugs are considered class B residues, which encompasses chemical substances that may represent a risk to public health and to the environment. Given the above, this research has the following objectives: to analyze how the population of Vitória da Conquista - BA performs the disposal of drugs in general. This is a descriptive, exploratory study of applied nature and a quantitative approach. An instrument with 11 questions was used for data collection, regarding the demographic and socioeconomic status of the participants, as well as their level of knowledge on the disposal of expired/unused drugs. The data collection was carried out at strategic points in the city, where there is a high flow of people living in different neighborhoods. 207 inhabitants over 18 years old and from both genders were interviewed, with the exclusion of children and teenagers, as these were less likely to be responsible for drug disposal in their households. For the organization and analysis of data collected through field research, the Microsoft Excel 2019 program was used. Among the interviewees, there was a predominance of female subjects (52,17%), considering that 51,82% of the population of Vitória da Conquista is female. The results found in this study demonstrate that the population of Vitória da Conquista disposes of drugs incorrectly. In conclusion, there is a knowledge deficit on appropriate disposal which originates from the lack of information on the topic, the shortage of take back locations and a lack of promotion of the environmental issues caused by the disposal.